DISCOURSE ON THE GENESIS OF PHILOSOPHY OF EDUCATION The philosophy of education is a specific area of philosophical knowledge, which - Nalivaiko, N. V.; Ashilova, M. S.; Begalinova, K. K. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The philosophy of education is a specific area of philosophical knowledge, which studies education and pedagogical activity on the part of content and methodology. Its formation takes place at the beginning of the twentieth century. And in this article the main reasons that caused the emergence of a new scientific direction – the philosophy of education – are analyzed. The authors examine various approaches to this complex problem, show the inseparable, organic connection between education, pedagogy and philosophy, reveal the common and distinctive features of these spheres of spiritual production. Education is considered as a process and result of mastering a person by a certain system of knowledge, skills and skills necessary for a full inclusion in the social and cultural life of society. And in this definition, the interrelation between education, culture, and philosophy is emphasized. The authors, based on the analysis of different approaches, come to the conclusion that the philosophical comprehension of education is a dictate of modern times, since modern education has passed the line when it can not already exist without the reflexive mechanisms necessary for the formation of an educational concept. This is only one of many reasons for the formation of the philosophy of education as an independent scientific discipline, which is shown in this article. Key words: education, philosophy of education, theory of education, pedagogical activity, culture, interdisciplinary theory, socialization, paradigm, systemic thinking, humanization.